Tourism and Island Society: Culture, Everyday Life, and Social Negotiation in Peripheral Island Communities - Dedy Iswanto (Professorline, 2026)
Tourism has become an increasingly influential force in shaping social and cultural life in island communities. Beyond its economic implications, tourism introduces new forms of interaction, representation, and negotiation that transform everyday life. This article examines tourism from a sociological and cultural perspective, focusing on how island societies experience, interpret, and respond to tourism development in their daily practices. Rather than treating tourism as an industry or development strategy, the article approaches it as a social process embedded in culture, space, and social relations. By foregrounding everyday life, it highlights how tourism reshapes meanings of place, identity, and social interaction in island contexts. The article contributes to discussions within art, culture, and society by examining tourism as a site where local values, external expectations, and social power intersect. This perspective offers a culturally grounded understanding of tourism in Global South island communities.